Analysis of Flood Disaster Management in Regional Medium-Term Development Plans: A Dynamic Governance Perspective - Reni Agustina Miftakul Janah; Septi Wulandari; Musta'ana (University of Merdeka Malang, 2026)
Flooding is a recurring disaster in Bojonegoro Regency, resulting in significant losses for the community and driving home the importance of adaptive and sustainable mitigation policies. This research aims to analyze the implementation of flood disaster management as outlined in the Bojonegoro Regency Regional Medium-Term Development Plan 2025-2029, using the perspective of dynamic governance, which focuses on organizational culture, government capabilities, and the capacity for policy change. The research employs a qualitative method with a case study design, involving an analysis of the Regional Medium-Term Development Plan document and in-depth interviews with relevant regional officials. The findings indicate that while the RPJMD includes comprehensive directions for flood mitigation, its implementation remains suboptimal in the aspects of Able People and Agile Process, primarily due to limitations in technical capacity and cross-sectoral coordination. Nevertheless, the dimensions of Thinking Ahead, Thinking Again, and Thinking Across are beginning to develop through the utilization of risk data, annual evaluations, and inter-agency cooperation. This research concludes that while the foundations of dynamic governance have been established, there is still a need to strengthen human resources, integrate information systems, and ensure consistency in the implementation of flood control programs.